Comparison of indoor air quality during sleep in smokers and non-smokers' bedrooms: a preliminary study - Canha, Nuno (2019)
People spend one third of their life sleeping, but the bedroom, as a specific micro-environment, is often neglected when assessing human exposure to air pollutants. However, exposure during sleep may be significant in the long-term to the integrated individual exposure. This study aimed to assess the exposure during sleep, focusing on a multi-pollutant approach (comfort parameters, carbon dioxide - CO2, carbon monoxide - CO, formaldehyde (CH2O), total volatile organic compounds (VOCs), particulate matter - PM2.5 and PM10 - and ultrafine particles, particle number concentrations - PNC - and lung deposited surface area - LDSA). For that, the air quality during sleep (in real conditions) was monitored using real-time devices in 12 bedrooms of urban (Lisbon and Vila Franca de Xira) and rural (Ponte de Sor) areas of Portugal for one night. Volunteers were smokers and non-smokers. Considering the Portuguese legislation for indoor air quality (IAQ), 67% of the bedrooms registered CO2 levels above the limit value, while CH2O, VOC, PM10 and PM2.5 thresholds were exceeded in 30, 100, 36, and 45% of cases, respectively. Regarding ultrafine parameters, LDSA and PNC ranged from 7.3 to 95.2 μm2/cm3 and from 0.6 to 4.8 × 103/cm3, respectively. Even with no smoking indoors, smokers' bedrooms were found to have significant higher levels of CO, CH2O, PM2.5, PM10 and LDSA than non-smokers' bedrooms, showing the effect of thirdhand smoke, exhalation of pollutants after smoking and infiltration on the degradation of the air quality in the bedroom. A recent new model of real-time monitor was also used for a wide set of IAQ parameters. Its performance to measure PM2.5 and CO2 was assessed, showing its applicability in real conditions. Although often neglected, these micro-environments should be considered in the integrated individual exposure to air pollutants and further studied. MAIN FINDINGS OF THE WORK: Several pollutants (CO2, PM, VOCs and CH2O) exceeded the guidelines during sleep; smokers are exposed to higher levels of CO, CH2O, PM, and LDSA than non-smokers while sleeping.